Dimensions of psychoanalysis - Sandler, Joseph (Karnac Books, 1989)
Dimensions of Psychoanalysis contains a selection of the Freud Memorial Lectures delivered by eminent British, French and American analysts at University College in the University of London. Together the papers form a powerful presentation of contemporary psychoanalytic thought, both Freudian and post-Freudian, in its relation to the profession itself and to the wider disciplines of sociology, the natural sciences and literature.